Patient preferences for management of high blood pressure in the UK: a discrete choice experiment - Fletcher, B; Hinton, L; McManus, R; Rivero Arias, O (Royal College of General Practitioners, 2019)
Background: With a variety of potentially effective hypertension management options, it is important to determine how patients value different models of care, and the relative importance of factors in their decision-making process.